2020
DOI: 10.1177/1533033820935531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Polo-Like Kinase 4 as a Marker for Advanced Tumor Stage and Dismal Prognosis in Patients With Surgical Gastric Cancer

Abstract: Objective: This study aimed to investigate the correlation of polo-like kinase 4 with clinicopathological features and survival profiles in patients with gastric cancer. Methods: This retrospective study was conducted based on the clinical data from 289 eligible patients with gastric cancer who received resection. Polo-like kinase 4 expression in adjacent tissue and tumor tissue was determined by immunohistochemical assay and semiquantified scoring method using immunohistochemical score by staining intensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The association of PLK4 expression with clinicopathological features has been previously investigated (13,32). For example, a previous study indicated that high PLK4 expression was associated with elevated T and TNM stages in patients with gastric cancer (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of PLK4 expression with clinicopathological features has been previously investigated (13,32). For example, a previous study indicated that high PLK4 expression was associated with elevated T and TNM stages in patients with gastric cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…The association of PLK4 expression with clinicopathological features has been previously investigated (13,32). For example, a previous study indicated that high PLK4 expression was associated with elevated T and TNM stages in patients with gastric cancer (32). However, the detailed association of PLK4 with the clinicopathological characteristics of patients with RCC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of PLK4 correlate with tumor growth, aggressive progression and treatment resistance representing a poor-prognostic marker. This accounts for a variety of malignancies including several epithelial cancer types (reviewed by [ 11 , 89 ]) such as breast cancer [ 196 , 197 , 198 , 199 ], lung cancer [ 200 , 201 ], prostate cancer [ 202 ], and gastric cancer [ 203 , 204 ], but also for neuroblastoma [ 205 ], glioblastoma [ 206 ], and acute leukemia [ 207 , 208 ]. In skin epidermis, overexpression of PLK4 leads to hyperplasia [ 209 ] and promotes—in association with p53 deficiency—tumorigenesis causing hyperproliferation and abnormal differentiation of basal keratinocytes and melanocytes [ 209 , 210 ].…”
Section: Plks and Tumor Developmentmentioning
confidence: 99%